2017
DOI: 10.1088/1741-2552/aa6806
|View full text |Cite
|
Sign up to set email alerts
|

An open source, wireless capable miniature microscope system

Abstract: Objective Fluorescence imaging through head-mounted microscopes in freely behaving animals is becoming a standard method to study neural circuit function. Flexible, open-source designs are needed to spur evolution of the method. Approach We describe a miniature microscope for single-photon fluorescence imaging in freely behaving animals. The device is made from 3D printed parts and off-the-shelf components. These microscopes weigh less than 1.8 g, can be configured to image a variety of fluorophores, and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 35 publications
1
121
0
Order By: Relevance
“…Importantly, due to recent technological advancements field studies are not necessarily as labor‐intensive as they used to be. As already mentioned, tracking can be to large extent automatized and even such techniques as single unit‐recordings, calcium imaging or optogenetics are already used in wireless fashion. However, more effort is still needed to optimize those technologies for the field application through improving both their robustness and availability.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, due to recent technological advancements field studies are not necessarily as labor‐intensive as they used to be. As already mentioned, tracking can be to large extent automatized and even such techniques as single unit‐recordings, calcium imaging or optogenetics are already used in wireless fashion. However, more effort is still needed to optimize those technologies for the field application through improving both their robustness and availability.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to existing open source software for animal tracking, PolyTouch is the only software that enables rapid (i.e.~5.7 ms) close-loop feedback for behavior (see Table 1 for a detailed comparison [23,26,60]. A direct comparison of PolyTouch with a customized video system revealed that the accuracy of PolyTouch is similar to manual offline tracking by an experienced human observer ( Figure 2E-F In terms of processing speed, modern closed-loop systems trigger feedback within 3-40 ms for neural data [11,13] and 12-50 ms for behavioral data [15,16,42,59,60] . PolyTouch can be used to control neural activity based on animal behavior at a temporal scale faster than synaptic communication along sensory pathways [61][62][63][64][65][66] , and thus could be used to create artificial sensory and motor feedback in the context of rapidly evolving behavioral computations [43,67] .…”
Section: Comparison To Existing Tracking Systemsmentioning
confidence: 93%
“…Recent technological advancements have enabled researchers to close the loop [9,10] with real-time experimental control of neural [11][12][13][14] and behavioral signals [15][16][17][18][19] . In particular, closed-loop optogenetic neural control has provided insight into cell-type-specific neuronal population dynamics in relation with seizure control [14,20,21] , sensory perception [22] , and spatial navigation [23] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, overexpression of GCaMP using AAVs can induce cell toxicity or even death (17). To overcome these potential limitations we built custom microendoscopes that were chronically implanted and performed long-term simultaneous bilateral imaging of hippocampal activity in freely moving Thy1-GCaMP6s mice (Figure 1a, S1, Movie 1 and 2, see supplementary data) (18)(19)(20)(21). The combination of chronic implants, high sensitivity microendoscope, improved cell detection and 25 registration with the CNMFe software allowed us to minimize motion artifacts and to increase the reliability of longterm recordings (Fig.…”
Section: Main Textmentioning
confidence: 99%